Emotional Geographies of an EFL Teacher in Asmat, Papua; Male Perspective - Sri Rejeki; Diah Kristina; Nur Arifah Drajati (International Journal of Language Teaching and Education, 2018)
Teaching is not only about knowledge, cognition, and skill but also emotional relationships among the students, colleagues, and parents. Particularly for teaching English in rural areas in Indonesia, there are several challenges that should be handled: geographical feature of these area, their culture and the way of life, the quality of both students and teachers, and so on. This research paper investigates teacher emotions experienced by a male EFL teacher in one of rural areas while dealing with those challenges. Teacher emotions are one of significant aspect that could not be left behind in teaching and learning activity. This research will explore comprehensively the distance and closeness felt by the teacher while teaching English there. This qualitative research was conducted using a narrative case study approach. The data were collected from the participant’s journal and interview. Referring to Hargreaves framework, the findings reveal 5 emotional geographies of the participant. This research contributes to Indonesian government as the one that concerns in 3T areas, EFL teachers who have to handle complex situations while teaching, and other researchers who are interested in conducting emotional geographic research.